2011
DOI: 10.1109/tnsre.2011.2116805
|View full text |Cite
|
Sign up to set email alerts
|

Time-Frequency Analysis of EEG Asymmetry Using Bivariate Empirical Mode Decomposition

Abstract: Abstract-A novel method is introduced to determine asymmetry, the lateralization of brain activity, using extension of the algorithm empirical mode decomposition (EMD). The localized and adaptive nature of EMD make it highly suitable for estimating amplitude information across frequency for nonlinear and nonstationary data. Analysis illustrates how bivariate extension of EMD (BEMD) facilitates enhanced spectrum estimation for multichannel recordings that contain similar signal components, a realistic assumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Theta oscillation was selected using EMD in Reference [43]. In Reference [44], the authors demonstrated a better localization of time-varying frequency components of mu and beta rhythms during motor imagery using the EMD algorithm. In their following work [45], they used an extension of the algorithm of EMD, named multivariate EMD (MEMD), to circumvent the problem of cross-channel interdependence in a 64-channel setup.…”
Section: Introductionmentioning
confidence: 99%
“…Theta oscillation was selected using EMD in Reference [43]. In Reference [44], the authors demonstrated a better localization of time-varying frequency components of mu and beta rhythms during motor imagery using the EMD algorithm. In their following work [45], they used an extension of the algorithm of EMD, named multivariate EMD (MEMD), to circumvent the problem of cross-channel interdependence in a 64-channel setup.…”
Section: Introductionmentioning
confidence: 99%
“…EMD is a fully data-driven method for decomposing a time series into AM/FM components which reflect its natural oscillations. As EMD makes no prior assumptions on the data it becomes suitable for the analysis of nonlinear and non-stationary processes (Huang et al 1998;Park et al 2011). The EMD algorithm extracts the IMFs using an iterative technique called "sifting" (Huang et al 1998).…”
Section: Empirical Mode Decomposition (Emd)mentioning
confidence: 99%
“…The HMS has been used by different authors after applying the Hilbert-Huang method to the EEG signal (Chen et al 2010;Li 2006;Li et al 2008;Chen et al 2016;Xiangjun et al 2017;Zhu et al 2015;Park et al 2011) but to our knowledge, the possible differences between the results obtained using the HMS and the conventional FFT spectra in resting conditions in healthy humans have not been studied in detail, and it results imperative, because for many years the universally used method for the spectral analysis of the EEG has used the FFT spectra. The advantages and possible limitations of the novel alternative approach, in this case the use of the HMS, could be better appreciated and could contribute to their more extended use in EEG investigations.…”
Section: Introductionmentioning
confidence: 99%
“…EMD-based noise removal method has been used recently in many fields such as biology, ocean, medicine, acoustics, fault diagnosis (Huang et al 1999; Liu et al 2006; Lee et al 2011; Park et al 2011; Ahrabian et al 2013; Moghtaderi et al 2013). It does not need to select the basis function in advance and has better adaptive feature.…”
Section: Introductionmentioning
confidence: 99%